Unraveling the Narrative of Orbital Cellulitis as a Sequelae to Trauma - Anilkumar S. Harugop; Aditya Achyut Redkar; Ajay Choondal; E. V. Manishaa (Journal of the Scientific Society)
Orbital cellulitis is often seen as a serious complication of acute rhinosinusitis. Facial trauma is one of the possible causes of orbital cellulitis. A middle-aged man, a mason by occupation, presented to ENT OPD following a facial trauma. He presented with a laceration over the right zygomatic region with right-sided periorbital swelling and redness. Wide-spectrum antibiotics were initiated for the patient. Pus was drained daily, and surgical debridement of the wound followed by sterile dressing of the wound cavity was done regularly until the pus discharge totally stopped. The patient was taken for secondary suturing and was discharged after that. However, the patient lost to follow-up. Facial trauma is a cause of orbital cellulitis. Orbital cellulitis is an emergency condition and requires urgent medical attention. Adequate antibiotic therapy is of utmost importance to treat the condition. Surgical care is advisable if the medical line of management fails.